1953
DOI: 10.1136/bmj.1.4802.136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pseudo-cholinesterase Level on Action of Succinylcholine in Man

Abstract: MMCMJORk cholinesterase available. However, it should be possible to increase the pseudo-cholinesterase of the plasma in the dog and thus to lower the concentration of free succinylcholine or suxethonium so rapidly that even the low concentration of the drug required for inhibition of the true cholinesterase in that animal will be effectively attacked. We therefore injected a highly concentrated solution of pseudo-cholinesterase intravenously into four dogs in the course of operations for mastectomy or conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1953
1953
2011
2011

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…O ccasional in d iv id u als how ever w hen given th e d ru g in its u su al dose show a m uch m ore prolonged response. Such people w ere fo u n d to h av e low er levels o f pseudocholinesterase a c tiv ity th a n w ere fo u n d in m o st o th e r people (B ourne, Collier and Somers 1952;E va ns, G ray, L ehm ann a nd S ilk 1952, 1953, a n d L ehm ann and R y a n (1956) observ ed t h a t low pseudoch o lin esterase levels m ig h t also be found am o n g som e o f th e ir im m e d ia te re la tiv es who w ere otherw ise h e a lth y . F a m ily stu d ie s (Lehm ann and R y a n 1956; Lehm ann and S im m o n s 1958; K a u fm a n , L ehm ann and S ilk 1960), led to th e hy p o th esis th a t su x a m e th o n iu m sen sitiv e in d iv id u als w ith low pseudocholinesterase a c tiv ity were hom ozygous for an unco m m o n gene, w hich in h eterozygotes also re su lte d in a d epression o f pseu d o ch o lin esterase levels b u t to a lesser degree.…”
Section: The Pseudocholinesterase Variants Esterase Levels and Dibucmentioning
confidence: 99%
“…O ccasional in d iv id u als how ever w hen given th e d ru g in its u su al dose show a m uch m ore prolonged response. Such people w ere fo u n d to h av e low er levels o f pseudocholinesterase a c tiv ity th a n w ere fo u n d in m o st o th e r people (B ourne, Collier and Somers 1952;E va ns, G ray, L ehm ann a nd S ilk 1952, 1953, a n d L ehm ann and R y a n (1956) observ ed t h a t low pseudoch o lin esterase levels m ig h t also be found am o n g som e o f th e ir im m e d ia te re la tiv es who w ere otherw ise h e a lth y . F a m ily stu d ie s (Lehm ann and R y a n 1956; Lehm ann and S im m o n s 1958; K a u fm a n , L ehm ann and S ilk 1960), led to th e hy p o th esis th a t su x a m e th o n iu m sen sitiv e in d iv id u als w ith low pseudocholinesterase a c tiv ity were hom ozygous for an unco m m o n gene, w hich in h eterozygotes also re su lte d in a d epression o f pseu d o ch o lin esterase levels b u t to a lesser degree.…”
Section: The Pseudocholinesterase Variants Esterase Levels and Dibucmentioning
confidence: 99%
“…Bourne (1953) suggested that the dose should be regulated by body weight, citing the work of Thesleff (1952), and thought that in " frail " patients this dose should be reduced. Evans et al (1952b) demonstrated an inverse relationship between this Ps.ChE. level and the duration of action of the relaxant, and later the same authors (1953) found that injections of a purified Ps.ChE.…”
Section: Hospitals)mentioning
confidence: 76%
“…It has been established that the drug is hydrolysed by serum pseudo-cholinesterase (Ps.ChE. ), and Bourne et al (1952), Evans et al (1952a), andBourne (1953) found low Ps.ChE. levels in the sera of patients showing delayed recovery.…”
Section: Hospitals)mentioning
confidence: 90%
“…Evans et al (17) are qmte definite that the low serum cholinesterase level is enough to explain the prolonged recovery time They, and Bourne, Somers ard Collier (16) between them have had eight cases ot somewhat prolonged apn0eas and in eadh one the serum cholinesterase was low. Lehmann (18) goes so far as to state that "to produce dramatic delay in recovery the enzyme level must obviously be ~ery low."…”
Section: Discussionmentioning
confidence: 99%